2023
DOI: 10.1109/jstars.2022.3220974
|View full text |Cite
|
Sign up to set email alerts
|

Panchromatic and Hyperspectral Image Fusion: Outcome of the 2022 WHISPERS Hyperspectral Pansharpening Challenge

Abstract: This paper presents the scientific outcomes of the 2022 Hyperspectral Pansharpening Challenge organized by the 12th IEEE Workshop on Hyperspectral Image and Signal Processing: Evolution in Remote Sensing (IEEE WHISPERS 2022). The 2022 Hyperspectral Pansharpening Challenge aims at fusing a panchromatic image with hyperspectral data to get a high spatial resolution hyperspectral cube with the same spatial resolution of the panchromatic image while preserving the spectral information of hyperspectral data. Four d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…However, some of the attempts have also been made in the literature, such as the fusion of hyperspectral with high-resolution multispectral or panchromatic bands 71 , 72 . But this does not necessarily guarantee an enhancement in the spatial resolution and there are a lot of challenges are associate with the integration of the spatial and spectral information 73 , 74 . Therefore, the current framework may be challenging for the detection of class categories with fewer land holdings as per the current spatial resolution (30 m) of Hyperion EO-1 and Landsat-8.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, some of the attempts have also been made in the literature, such as the fusion of hyperspectral with high-resolution multispectral or panchromatic bands 71 , 72 . But this does not necessarily guarantee an enhancement in the spatial resolution and there are a lot of challenges are associate with the integration of the spatial and spectral information 73 , 74 . Therefore, the current framework may be challenging for the detection of class categories with fewer land holdings as per the current spatial resolution (30 m) of Hyperion EO-1 and Landsat-8.…”
Section: Resultsmentioning
confidence: 99%
“…With this study, it has also been observed that neural network has more potential in handling high-dimensional datasets and solving real-time complex problems. The deep neural networks or incorporation of subpixel-based classifiers may solve the problem of mixed pixel interference and handle large volumes of data in real time 74 76 The subpixel-, pixel-, and superpixel-based image fusion methods may also be followed to improve the detection of land surface changes via the hyperspectral dataset 77 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ECENTLY, the remote sensing image interpretation methods covering panchromatic image [1], [2], multispectral images [3], [4] and hyperspectral images (HSIs) [5] have achieved remarkable achievements. Among them, HSIs can provide rich spectral information (i.e., about 10-nm spectral resolution), which makes it possible to identify the ground objects with different characteristics by means of the spectral information [6].…”
Section: Introductionmentioning
confidence: 99%